Kepatuhan Hak Asasi Manusia dalam Praktik Penyidikan oleh Aparat Penegak Hukum: Analisis Kuantitatif di Indonesia - Faisal; Qustontiniyah, Ulfatul; Ghofur, Muhammad Jamal Udin (Universitas Sains dan Teknologi Komputer, 2024)
This study examines the compliance of law enforcement officers with human rights (HR) principles during investigative practices in Indonesia using a quantitative approach. Despite Indonesia's commitment to HR protection, significant gaps persist in the enforcement of rights, such as access to legal counsel and humane treatment. The study aims to evaluate the level of HR compliance, identify influencing factors, and propose actionable solutions to improve investigative practices. The research employed a survey methodology involving 400 respondents, including law enforcement officers, suspects, witnesses, and lawyers. Key indicators analyzed include the treatment of detainees, the right to information, access to legal representation, and mechanisms for reporting HR violations. The collected data were analyzed statistically using descriptive and inferential methods to identify compliance patterns and underlying factors. Findings reveal that HR compliance during investigations remains moderate. While 62% of respondents acknowledged adherence to the right to information, only 45% reported consistent access to legal representation, and 38% experienced inhumane treatment. Factors such as officer training, independent oversight mechanisms, and the integration of technology positively influence compliance. However, challenges like case resolution pressure and limited public awareness of reporting mechanisms hinder broader compliance. The study contributes theoretically by highlighting the multifaceted nature of HR compliance, emphasizing the roles of training, oversight, and technology. Practically, it provides recommendations for policymakers to enhance HR-focused training, promote the use of technology in investigations, and improve the accessibility and transparency of reporting systems. Limitations include geographical constraints and potential biases in self-reported data, suggesting avenues for future research to adopt longitudinal approaches and broader samples. This research advances understanding of HR compliance in law enforcement and offers practical insights for fostering fair and HR-centered investigative practices in Indonesia.